Аналітичне та імітаційне моделювання системи масового обслуговування на прикладі сервісного центру технічної підтримки комп’ютерів - Скляренко Олена; Skliarenko Оlena; Терещук Ганна Михайлівна; Tereshchuk Hanna; Ніколаєвський Олександр; Nikolaievskyi Oleksandr; Скляренко Олег; Skliarenko Oleh (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У статті досліджується вплив аналітичного та імітаційного моделювання на ефективність функціонування сервісних центрів технічної підтримки комп’ютерної техніки в умовах зростання попиту на ІТ-послуги та ускладнення структури систем масового обслуговування (СМО). Розглядається актуальність застосування математичних методів для оптимізації структури автоматизованих сервісних систем, зокрема з метою скорочення часу очікування, підвищення ймовірності миттєвого обслуговування заявки та зменшен-ня кількості відмов.У дослідженні запропоновано поєднання аналітичного підходу з імітаційним моделюванням, що дозво-ляє комплексно аналізувати функціонування СМО на основі моделей типу M|M|1 та стохастичних мереж Петрі. Виявлено, що таке поєднання забезпечує високу точність прогнозування навантаження, дозволяє виявити вузькі місця системи, сформувати оптимальну структуру обслуговування та приймати обґрунтовані управлінські рішення. Продемонстровано використання моделювання для визначення критичних параметрів і оцінювання ефективності роботи системи. /// EN: The article examines the impact of analytical and simulation modeling on the operational efficiency of computer technical support service centers under the conditions of increasing demand for IT services and the growing complexity of queuing system (QS) structures. The relevance of applying mathematical methods to optimize the structure of automated service systems is discussed, particularly with the aim of reducing waiting times, increasing the probability of immediate request processing, and minimizing rejection rates.The study proposes a combination of analytical and simulation modeling approaches, enabling a comprehensive analysis of QS performance using M|M|1 models and stochastic Petri nets. This integrated approach ensures high-precision workload forecasting, identification of system bottlenecks, formation of an optimal service structure, and data-driven decision-making.The article outlines the request handling mechanisms within a service center, which include three stages: registration, diagnostics, and repair, taking into account the possibility of stream thinning at each phase. The use of modeling for identifying critical system parameters and evaluating performance is demonstrated.Particular attention is paid to the practical significance of modeling, namely its ability to enhance service reliability and performance, as well as adapt to variable conditions and unstable incoming requests. The findings can be applied to improve service quality in support centers and to implement innovative management approaches in the IT support.The integration of these modeling techniques facilitates the analysis of resource allocation scenarios and their impact on service continuity. The approach allows for stress testing of system capacity under peak loads, offering valuable insights for contingency planning. Simulation experiments based on real-time parameters enable a more accurate depiction of dynamic behavior within queuing environments. This ensures that management strategies are not only theoretically sound but also practically feasible and responsive to real-world challenges.
Analytical and simulation modeling of a queuing system based on the case of a computer technical support service center
Keywords: истеми масового обслуговування; аналітичне моделювання; імітаційне моделювання; стохастичні мережі Петрі; queuing systems; analytical modeling; simulation modeling; stochastic Petri nets